Modulation of Gut Microbiota and Oxidative Status by β-Carotene in Late Pregnant Sows - Yuan, Xupeng; Yan, Jiahao; Hu, Ruizhi; Li, Yanli; Wang, Ying; Chen, Hui; Hou, De-Xing; He, Jianhua; Wu, Shusong (Frontiers in Nutrition, 2020)
Recent evidences suggest that gut microbiota plays an important role in regulating physiological and metabolic activities of pregnant sows, and β-carotene has a potential positive effect on reproduction. This study aimed to explore the effect and mechanisms of β-carotene on reproductive performance of sows from the aspect of gut microbiota. A total of 48 hybrid pregnant sows (Landrace × Yorkshire) with similar parity were randomly allocated into 3 groups (n=16) and fed with a basal diet or a diet containing 30-90 mg/kg of β-carotene from day 90 of gestation until parturition. Dietary supplementation of 30 mg/kg or 90 mg/kg β-carotene increased the number of live birth to 11.82±1.54 and 12.29±2.09, respectively, while the control group was 11.00±1.41 (P = 0.201). Moreover, β-carotene increased significantly the serum nitric oxide (NO) level and glutathione peroxidase (GSH-Px) activity (P < 0.05). Characterization of fecal microbiota revealed that 90 mg/kg β-carotene increased the diversity of the gut flora (P < 0.05). In particular, β-carotene decreased the relative abundance of Firmicutes including Lachnospiraceae AC2044 group, Lachnospiraceae NK4B4 group and Ruminococcaceae UCG-008, but enriched Proteobacteria including Bilophila and Sutterella, and Actinobacteria including Corynebacterium and Corynebacterium 1 which are related to NO synthesis. These data demonstrated that β-carotene may improve the reproductive performance by increasing antioxidant capacity and the production of NO, an important vasodilator to promote the neonatal blood circulation, through regulating gut microbiota in sows.